EVALUASI KETAATAN PENULISAN KARTU OBAT TERHADAP FORMULARIUM RUMAH SAKIT DI RSUD UNGARAN KABUPATEN SEMARANG TAHUN 2008 - Mohammad Djatmiko; Riharti Sulastini (Universitas Wahid Hasyim Semarang, 2010)
ABSTRACT Hospital formulary is a list of drugs selected that appropriate and economically used as a guide in prescriptions in the hospital. Non-compliance resulted in patients getting the drug formulary that is not timely because the drug is not available in the pharmacy department. Evaluation of adherence to the formulary drug card writing is closely related to the rational use of drugs. This study aims to determine the level of adherence to the formulary drugs written in Ungaran Hospital. This research is a non experimental and data were analyzed descriptively and non-analytic by cluster random sampling technique. Results showed that the use of the drug on patient counted 457 kinds comprising 95.7% of drug patents and generic drugs 4.3%. Conformity with the standard drug formulary, 79.6%. The highest conformity of drug use with formularies is the unit of pharyngeal, nose and ear 99.1%. Whereas based on therapeutic class are antiinflammatory therapy antirheumatic 100%. Drug use in hospitalized patients as much as 423 kinds of patent medicine consisting of 99.8% and 0.2% of generic drugs. Conformity with the standard drug formulary, 74.9%. The highest conformity of drug use with formularies is the unit of Neural 92.6%. Whereas based on therapeutic class are antiinflammatory therapy antirematik 100%. Key words : evaluation of adherence, hospital formulary